Effect of application frequency of oil palm fronds (Elaeis guineensis Jacq.) local microorganisms on the growth of Eucalyptus grandis CGP 105 seedlings - Azmi, Yudia; Batu, Melfa Sulvia Lumban; Arrozi, Nursyam (Research and Social Study Institute, 2023)
This study aims to determine the effect of application frequency of oil palm fronds’ local microorganisms (LMO) on the growth of Eucalyptus grandis CGP 105 seedlings, and to determine the application frequency that produce the best growth on Eucalyptus grandis CGP 105 plants. This study applied Randomized Block Design consisting of 5 treatments and 4 replications, namely P0: without LMO (control), P1: 1 time of application (7 days after planting/DAP), P2: 2 times of application (7 and 14 DAP), P3: 3 times of application (7, 14, and 21 DAP), and P4: 4 times of application (7, 14 , 21, and 28 DAP). The parameters observed were plant height (cm), leaf length (cm), leaf width (cm), number of leaves (strands), and stem diameter (mm). Based on ANOVA results at the 5% level, the application of oil palm fronds’ LMO on Eucalyptus grandis CGP 105 seedlings had a significant effect on all measured parameters. The best application frequency of oil palm fronds’ LMO is P4 treatment, which resulted in the average of plant height of 25.83 cm, leaf length of 7.47 cm, leaf width of 3.54 cm, number of leaves of 13.25 strands, and stem diameter of 2.45 mm. Penelitian ini bertujuan mengetahui pengaruh frekuensi pemberian mikroorganisme local (MOL) pelepah kelapa sawit (Elaeis guineensis Jacq.) terhadap pertumbuhan bibit Eucalyptus grandis CGP 105, serta mengetahui frekuensi pemberian MOL yang menghasilkan pertumbuhan terbaik pada tanaman Eucalyptus grandis CGP 105. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) yang terdiri dari 5 perlakuan dan 4 ulangan, yaitu P0: tanpa MOL (kontrol), P1: 1 kali pemberian (7 hari setelah tanam/HST), P2: 2 kali pemberian (7 dan 14 HST), P3: 3 kali pemberian (7, 14, dan 21 HST), dan P4: 4 kali pemberian (7, 14, 21, dan 28 HST). Parameter yang diamati meliputi tinggi tanaman (cm), panjang daun (cm), lebar daun (cm), jumlah daun (helai), dan diameter batang (mm). Hasil uji ANOVA pada taraf 5% menunjukkan bahwa pemberian MOL pelepah kelapa sawit pada bibit Eucalyptus grandis CGP 105 berpengaruh terhadap semua parameter yang diamati. Frekuensi pemberian MOL pelepah kelapa sawit terbaik adalah perlakuan P4, yang menghasilkan rerata tinggi tanaman 25,83 cm, panjang daun 7,47 cm, lebar daun 3,54 cm, jumlah daun 13,25 helai, dan diameter batang 2,45 mm.